Islamic Economic Perspectives on Global Economic Integration: A Theoretical Framework - Putri, Nurul Wulandari; Prabuwono, Anton Satria (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Globalization certainly has a significant impact on the lives of Indonesian people. This impact includes two aspects, namely positive and negative. The influence of globalization has also penetrated all areas of life, including politics, economics, thought, and socio-cultural life. With its concept of Sharia economics, Islam is present at the right time and is warmly welcomed by the community. Islamic economics seems to be at least considered an alternative answer to the chaos of economic globalization. Objective: This study examines whether Islamic Economics can be an alternative answer to the increasingly complex chaos of economic globalization. Method: This study uses Library Research, commonly called a literature review. The data is obtained from various related literature, which is classified and analysed using a critical philosophical approach. Result: The results show that the concept of Islamic economics aims to achieve Maqasid Shari'ah, which includes the fulfilment of five basic needs (al-ḍaruriyat al-khams), namely the protection of religion, soul, mind, offspring, and property. To achieve this goal, steps that need to be taken include revitalization of the human element, reduction of wealth concentration, economic restructuring, and fiscal restructuring. Implication: This research provides an understanding that Islamic economics has the potential to be an effective alternative in dealing with the inequalities and challenges posed by the global economy.